Notebook of exercises for potential the offensive-tactical thought in the athletes of basketball juvenile category of the Guantanamo province - Liuver Burke-Marsan; Alexander Castellanos-Columbié; Tomás Martínez-Tabera (Universidad de Guantánamo, 2018)
The research deals with a topic of vital importance to enhance the offensive-tactical thinking in the youth basketball athletes of Guantanamo province. It will contribute to the development of high performance sport, to a certain extent, based on the proposal of the designed exercises. In the work is characterized in a general way to the specific one, the training process of the offensive-tactical foundations in basketball, it is supported by the orientations derivate from the current training program of preparation of the athlete. Besides, is done a systematization of the theoretical foundations that support the tactical preparation in basketball, from the fundamental transformations that arise in this specialty of high performance sports.